Electronic versus conventional spatiotemporal image correlation (STIC) fetal echocardiography: a direct comparison. (3rd April 2022) - Pepes, Spiridon; Parthenakis, Fragiskos; Makrigiannakis, Antonis; Germanakis, Ioannis
Abstract: Objectives: Recent advances in Spatial Temporal Image Correlation (STIC) 4 D fetal echocardiography include the application of eSTIC based on electronic probe image acquisition. We aimed to directly compare the performance of conventional STIC versus eSTIC technique (B-Mode and color Doppler imaging) during off-line reconstruction of STIC/eSTIC fetal heart volume pairs. Methods: Pairs of B-Mode and Color Doppler STIC volumes were acquired sequentially by firstly conventional (STIC) followed by electronic (eSTIC) probes during 33 consecutive obstetric scans at median 23 (range 13–31) gestational weeks. The resulting 66 fetal heart volume pairs were assessed blindly off-line by a fetal cardiologist who documented feasibility of reconstruction, presence of motion artifacts, subjective image quality on a 4-level scale: 1-best to 4-non-diagnostic and morphological diagnosis, to enable a paired comparison of STIC and eSTIC in the same fetus under similar scanning conditions. Results: eSTIC volumes had higher temporal resolution (37 vs. 24 frames per second, p < .001), less motion during acquisition (12 vs. 20 cases, O.R. 7.0, p = .002) and better average image quality (1.9 vs. 2.2, p = .006) compared to STIC volumes. More diagnostic reconstructions were achieved by eSTIC ( n = 55, 86%) than STIC ( n = 52, 78.8%), p = .001), in a comparable analysis time (mean 4.96 vs. 4.94 min). During a comparison of image quality of the original acquisition (A) and reconstructed planes (B and C planes) e STIC was superior in 22 (33%), 39 (59%) and 21 (38%) volumes, respectively, with the remaining cases being of similar quality (<10% in each plane in favor of STIC). Imaging mode and gestational age had a similar impact on both eSTIC and STIC performance: diagnostically acceptable studies in 49 (75.8%) vs. 48 (72.2%) by B-Mode, 60 (90.9%) vs. 56 (84.8%) by Color Doppler Mode, 8 (62.5%) vs. 10 (50%) in early scans, 38 (95%) vs. 38 (95%) in mid-gestation scans, and 7 (70%) vs. 6 (60%) in third trimester scans. Eight obstetric scans identified a fetus with a cardiac variant or structural abnormality. Diagnostic concordance of the two STIC approaches was comparable (40/48 concordant interpretations, kappa 0.657) all confirmed by fetal and/or postnatal echocardiography. Conclusions: eSTIC was associated with more effective 4 D fetal heart reconstruction due to reduced motion artifacts and superior image quality in all planes, when compared to STIC. Early gestation reconstructions were not generally successful using either technology. Further study is needed to define the cost-effectiveness and diagnostic impact of eSTIC over conventional STIC and their role over, or in addition to, screening 2 D fetal echocardiography by appropriately trained sonographers.